Geologic and hydrological controls on coal reservoir water production in marine coal-bearing strata: A case study of the Carboniferous Taiyuan Formation in the Liulin area, eastern Ordos Basin, China. (January 2015) - Xu, Hao; Tang, Dazhen; Tang, Shuheng; Zhang, Wenzhong; Meng, Yanjun; Gao, Lijun; Xie, Shizhang; Zhao, Junlong
Abstract: Coalbed methane (CBM) is commercially explored and produced in the continental Permian Shanxi Formation of the southern Qinshui and eastern Ordos Basins of China. However, CBM production in marine Carboniferous Taiyuan Formation is hindered by a lack of knowledge about the controlling factors on water production. The Liulin area of the eastern Ordos Basin is one of the trail areas for CBM development in China. In this study, water yield characteristics and their influencing factors during CBM production in the Liulin area were investigated by fluid inclusion studies, core slice observations, and stable isotope analyses of groundwater. The results demonstrated that the recharge area for this limestone aquifer of the Taiyuan Formation is the exposed carbonate in the northeastern Liulin area. The thickness along with the dissolved pores and fractures of the limestone aquifer were closely related to the water production of the CBM well. From an engineering point of view, hydraulic fracturing allows the direct movement of water from coal seams to the roof limestone aquifers, which was a key factor in the high water yield of CBM wells in the Liulin area. Finally, based on the structure and distribution of roof limestone as well as water production data, the geologic scenarios for water production in the Taiyuan Formation was divided into four types. These divisions indicated that the best prospective target areas for CBM production should have low numbers of faults, small limestone thicknesses, relatively large burial depths and normal reservoir pressures and temperatures. The results of this study are helpful for CBM exploration and production in the marine coal-bearing strata of China. Highlights: Thickness, dissolved pores and fractures of limestone influenced water production. Hydraulic fracturing was a key engineering factor for the high water yield. The geologic scenarios for water production were divided into four types. Favorable geological conditions for CBM production were summarized.